1998
DOI: 10.1021/bi9809270
|View full text |Cite
|
Sign up to set email alerts
|

Using Matrix-Assisted Laser Desorption Ionization Mass Spectrometry To Map the Quinol Binding Site of Cytochrome bo3 from Escherichia coli

Abstract: The cytochrome bo3 ubiquinol oxidase contains at least one and possibly two binding sites for ubiquinol/ubiquinone. Previous studies used the photoreactive affinity label 3-[3H]azido-2-methyl-5-methoxy-6-geranyl-1,4-benzoquinone (azido-Q), a substrate analogue, to demonstrate that subunit II contributes to at least one of the quinol binding sites. In the current work, mass spectroscopy is used to identify a peptide within subunit II that is photolabeled by the azido-Q. Purified cytochrome bo3 was photolabeled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
39
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 28 publications
0
39
0
Order By: Relevance
“…16 Wild-type bo 3 enzyme with bound UQ 8 was purified as described previously. 29 Native UQ 8 was removed by purification of QOX using N,N-dimethyldodecylamine N-oxide (LDAO) as the detergent, followed by detergent exchange with n-dodecyl-b-D-maltoside (b-DM). Reconstitution with exogenous 2,3-dimethoxy-5,6-dimethyl-1,4-benzoquinone (DDQ, see Fig.…”
Section: Sample Preparationmentioning
confidence: 99%
See 3 more Smart Citations
“…16 Wild-type bo 3 enzyme with bound UQ 8 was purified as described previously. 29 Native UQ 8 was removed by purification of QOX using N,N-dimethyldodecylamine N-oxide (LDAO) as the detergent, followed by detergent exchange with n-dodecyl-b-D-maltoside (b-DM). Reconstitution with exogenous 2,3-dimethoxy-5,6-dimethyl-1,4-benzoquinone (DDQ, see Fig.…”
Section: Sample Preparationmentioning
confidence: 99%
“…22 Variant cytochrome bo 3 ubiquinol oxidase from E. coli containing one equivalent of bound UQ 8 was purified in n-dodecyl-b-D-maltoside according to the method described previously, 28 and concentrated to approximately 0.1 mM in 100 mM K-Phosphate buffer at pH 8. The presence or absence of ubiquinone was confirmed by FTIR spectroscopy as reported in 31 (data not shown).…”
Section: Sample Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, using depth-dependent fluorescent ubiquinone analogues, Miyoshi et al (17) demonstrated that the ubiquinone-reduction site of GDH is located close to the membrane surface rather than in the hydrophobic interior. X-ray crystallographic structures of cytochrome bo in E. coli (18,19) and cytochrome bc 1 complex (Q o and Q i centers) in bovine heart mitochondria have recently been determined (20, 21), and it has been indicated that their ubiquinone-binding sites may be close to the membrane surface. Thus, it seems reasonable that the ubiquinone-reacting site of GDH is located near the membrane surface.…”
mentioning
confidence: 99%